Aspects on advanced procedures during endoscopic retrograde cholangiopancreatography for complex hepatobiliary disorders - Lubbe, Jeanne Adele (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.